CONSTRUCTIONS AND OBSTRUCTIONS OF TEACHER EXPLANATION TO STUDENTSÃ¢â¬â¢ LEAR-NING: PERSPECTIVES OF STIBA SATYA WACANA STUDENTS - Debora Tri Ragawanti (TEFLIN Journal: A publication on the teaching and learning of English, 2007)
This study investigated learnersÃ¢â¬â¢ perspectives on how a teacher explanation can facilitate or hinder their learning. The results suggested that teacherÃ¢â¬â¢s use of mixed L1 and L2 in an explanation is preferred by most student-respondents since it can expedite their learning. Using only L2 is also preferred because students believe that it gives them more exposure to English and as English department students, they have to use English. It, however, can impede learning when teachers use difficult words or complicated grammar. In this condition, using simple language helps students understand an explanation. Despite teacherÃ¢â¬â¢s use of language, learnersÃ¢â¬â¢ perspectives on teacherÃ¢â¬â¢s behaviors when explaining showed that rapid speaking rate can hinder the process of internalizing an explanation. Conversely, slowing down speech rate can promote a comprehensible input. Toward the use of examples, using examples from daily life is more preferred than the ones presented in the text book since such examples are easy to remember and understand. Lastly, teacherÃ¢â¬â¢s use of humor is perceived to motivate studentÃ¢â¬â¢s learning through relaxed and enjoyable atmospheres. It also helps remember language chunks through which it will be an intake. However, humor can obstruct learning if students focus more on the humor than the lesson.